If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(y + -6) = -70 Reorder the terms: -7(-6 + y) = -70 (-6 * -7 + y * -7) = -70 (42 + -7y) = -70 Solving 42 + -7y = -70 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + -7y = -70 + -42 Combine like terms: 42 + -42 = 0 0 + -7y = -70 + -42 -7y = -70 + -42 Combine like terms: -70 + -42 = -112 -7y = -112 Divide each side by '-7'. y = 16 Simplifying y = 16
| 4x-(5x-6)= | | 3a+5b-7a-2b= | | 5x+3-6x=0 | | 5x+3-6c=0 | | 32xy=236 | | 8x^4+6x^2-2= | | 5-(15x-1)=13x | | -11-3x=44 | | 9x/4=5/7 | | 30000/7500 | | 20x+10(2x)+10x+1(5x)=750 | | y=5+x^2+2x | | -5-2n=-2(1+n)-3 | | v+4.74=7.4 | | 18/3=v/7 | | 8(x-7)=-24-8x | | 64-x^6= | | 6(v-1)-6=-7(-4v+1)-7v | | 5y+2=3y+22 | | -3(-4-2n)=19+6n | | y+2=23(x-9) | | Y=10c | | t=(x-1)(1-x) | | 8/3y=5/6x-2 | | 20log(x)=-12 | | -62=1-9w | | -39-2x=7x-6(1+7x) | | X^2+6x=59 | | 8v=2(4v+-2) | | -3x+50=2x+10 | | -12=-2(x+5) | | In(2x)=-2 |